Spatiotemporal patterns of commercial activities in Exarchia-Neapoli area - Ioanna Chatzikonstantinou; Stavroula Katsiampoura (European Journal of Geography)
The focus of this paper is the analysis of spatio-temporal patterns of commercial activities in the area of Exarchia-Neapoli, in Athens, during the last decade. A significant downturn during the financial crisis has left its mark on commerce along with all other sectors of the economy in Greece. However, there is poor geographical analysis up to this date, depicting the changes in spatial concentration and dispersion of shops, flourishing and decaying sectors and their spatial footprint. The main purpose of this study is to reveal these transformations in a central mixed-use neighborhood of Athens. The type of commercial activity of ground floor stores and offices in the area is recorded at three different points in time (2009, 2014, 2019). After the collection and categorization of data, spatial analysis was carried out using geostatistical indicators such as mean center and standard deviational ellipse and spatial patterns were determined through nearest neighbor analysis. ?he analysis over space and time reveals trends and patterns of clustering and avoidance respectively, both within commercial uses and between different ones. Furthermore, their correlation with the centrality of the network (space syntax analysis) reveals not only proximity relationships, but also their strength and resilience over time. Finally, we discuss our findings in relation to the dynamics of commerce in the Exarchia area and propose scaled-up research opportunities.